Osteochondroma at the Ventro-Medial Surface of the Scapula Causing Pseudo Winging Scapular Resection with Computer-Assisted Navigation: A Case Report and Literature Review - Nakornnoi, Teerapat (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Osteochondromas, the most common benign bone tumors, primarily occur in the long bones, with scapular osteochondromas constituting less than 1% of cases. A unique challenge in ventral scapular osteochondromas is limited visibility from the dorsal side. Computer-assisted surgery, which is widely employed in tumor surgery is a promising solution for minimally invasive resection with reduced muscle injury. Methods: We present the case of a thirteen-year-old female with a ventral scapular osteochondroma that cause winging and snaping of her left arm. The patient underwent computer-assisted surgery under general anesthesia in the prone position. The procedure involved a minimal incision over the crest of the scapular spine, enabling precise identification of the tumor from the dorsal side using navigation tools. Results: The tumor, identified as an osteochondroma on CT scans, was successfully resected with minimal soft tissue damage. Postoperatively, the patient's arm was immobilized for two weeks, followed by a pain-free return to normal activity. Radiographic evaluation confirmed complete tumor removal. Conclusions: Computer-assisted navigation can help locate the ventral osteochondroma of the scapula with minimal soft tissue damage and a quicker recovery time.